Calidad micológica del aire en el Mercado Belén y Central de la ciudad de Iquitos, Loreto, Perú-2021 - Lozano Dávila, Xiome Antuane (2022)
The present study was carried out in the Belen Market and the Central Market of the city of Iquitos with the purpose of evaluating the mycological air quality. The passive sedimentation method described by Omeliansky was used, for which Potato Dextrose Agar (PDA) was used, the plates with the medium were exposed for 15 minutes in the open air and then incubated at room temperature for 5 days, and then the measurements were recorded. Macroscopic characteristics of the colonies that were subsequently isolated on plates where pure colonies were obtained. For microscopic observation, the humid chamber technique was performed. In the results of the investigation, 688 colonies were isolated where 22 genera and/or species of environmental fungi were identified. Among the most frequent genera and/or species we have yeast (80.36%), Sterile Mycelium (76.79%) and Penicillium sp (73.21%) being according to the classification scale as common, and those with the highest relative density to yeast, Penicillium sp and Sterile mycelium with 37% (232 colonies). It was determined that both environments present a high level of mycological contamination, which was obtained from the concentration of environmental fungi, a total of 672,141 CFU/m3 is reported in the Belén Market and 615.973 CFU/m3 in the Central Market.